Content of consent to transaction - Iu.S. Povarov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to a systematic study of the content aspect of giving consent to a transaction in the context of the need to comply with the requirement for the certainty of such consent. The legislative requirements regarding the content of consent, differing depending on its type (preliminary or subsequent), have been described in detail. Particular attention has been paid to the problems associated with the interpretation of the term “subject of the transaction”; two main interpretational approaches (broad and narrow) have been singled out and studied, and the logic of the narrow vision based on the consideration of the subject of the transaction as the most important but not the only essential condition has been argued for reasons of formal legal and substantive order. The classification of the conditions of consent turns out to be as follows: a) based on their substantive focus – main and additional (or accidental) conditions associated with the “organizational” moments of the transaction; b) by the criterion of the need for indication – mandatory (or objectively significant) and optional (or subjectively significant). An accredited optional condition, in particular, is the provision on the duration of the consent; but we have justified the expediency of dispositive regulation of this issue by law. As a perspective direction of scientific research, the problem of consequences of non-compliance with the content of consent has been assessed; as a general approach, the thesis of the absence in this case of consent (the failure to have an appropriate legal effect) has been derived.